“THE ROLE OF ARTIFICIAL INTELLIGENCE IN THE IMPROVEMENT OF HUMAN INTERPERSONAL COMMUNICATION” - Eligino , Jennallyssa Marie A.; Valderama , Louisa; Ajos, Juliet; Aguire , Ricardo; Tolentino , Jozelle; Baquiler, Arabelle (International Journal of Psychosocial Rehabilitation, 2020)
Technology has become a tool for simplifying communication. The world is no longer bounded by geographical restrictions and there is no limit to how much messages people can send. With just one or multiple clicks, people can easily connect. Aside from that, there is more than one method to contact, a variety of communication content, and a bigger audience to influence (Sharma, 2018). Despite these, there are also criticisms on technology, stating that it hinders the quality of interpersonal communication. This claim is only subjective and is based on fear of change, especially those who are in areas who have not yet embraced the benefits of technology (The NYU Dispatch, 2018).